Degradable elastomer material, preparation method thereof and uterine cavity stent
The degradable elastomer material prepared by emulsification method is used to make uterine cavity stents, which solves the problems of readhesion and non-degradation of IUD after uterine cavity adhesion separation, and achieves complete degradation of stents and protection of the inner lining of uterine cavity. .
Patent Information
- Application Number
- CN202411403714.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, the probability of readhesion after uterine adhesion separation surgery is high, and the commonly used IUDs are not degradable, have a small size and require secondary removal.
A method of preparing a degradable elastomer material is adopted to prepare pores by emulsifying the method to prepare pores and is used to make uterine cavity stents. The material consists of degradable polymer material and degradable metal powder. By adjusting the composition and porosity of the composite material, the degradation rate of the material is adjusted.
Complete degradation of the uterine cavity stent is achieved without secondary removal, reducing the risk of readhesion and avoiding wear or puncture damage to the inner wall of the uterine cavity.
Smart Images

Figure CN119455141A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of medical devices, and in particular relates to a degradable elastomeric material, a preparation method thereof and a uterine cavity stent. Background Art
[0002] Intrauterine adhesion is a common gynecological disease, also known as intrauterine adhesions and intrauterine adhesion syndrome. Generally, due to radiotherapy, intrauterine surgery, low estrogen status and infection, the basal tissue structure of the endometrium is destroyed and the endometrium loses its regenerative function, resulting in adhesions between the cervical canal and uterine wall. The occurrence of intrauterine adhesions often leads to amenorrhea, infertility, reduced menstrual volume, cyclical abdominal pain, miscarriage, etc. in women of childbearing age, which greatly endangers the health and quality of life of the majority of women. At present, hysteroscopic intrauterine adhesion separation is used as the main treatment method in clinical practice. Under the visualization of hysteroscopy, minimally invasive surgery is used to separate the adhesion site and restore the morphology of the uterine cavity. However, the probability of re-adhesion after surgery is high. According to statistics, about 62.5% of patients will have intrauterine adhesions again after intrauterine adhesion separation. Therefore, how to reduce re-adhesion after hysteroscopic adhesion separation is the focus of attention in the industry and a thorny problem faced in clinical practice. At present, the main method of placing a balloon or an IUD in the uterine cavity after surgery is to avoid the postoperative adhesion of the uterine cavity tissue wound surface and the occurrence of adhesion. After the separation of intrauterine adhesions, the placement of a balloon can achieve a physical barrier effect. However, the shape of the balloon makes it difficult to separate the complex curved surface structure of the uterine cavity, and the intrauterine pressure of the water balloon is not easy to control, which may cause excessive local pressure and lead to ischemic necrosis of the endometrium in this area. In addition, the inserted balloon has an external catheter, and long-term implantation is prone to cause intrauterine infection. Shortening the implantation time and taking antibiotics are often used for auxiliary treatment. Therefore, balloon implantation brings great safety risks and low applicability to patients. In addition, intrauterine contraceptive devices are also commonly used as a treatment for preventing intrauterine adhesions. However, the intrauterine contraceptive devices commonly used in clinical practice are copper-containing metal devices, which are non-degradable and small in size. They cannot well separate the adhesion of the uterine cavity wall tissue and need to be removed twice. Summary of the invention
[0003] The present invention provides a degradable elastomeric material and a preparation method thereof, and a uterine cavity stent, so as to solve the problems in the prior art that common clinical intrauterine contraceptive devices are non-degradable, small in size, and require secondary removal.
[0004] To achieve the above object, the present invention proposes the following technical solutions:
[0005] A method for preparing a degradable elastomeric material comprises the following steps:
[0006] Step 1, dissolving the degradable polymer material with an organic solvent to prepare a uniformly dissolved polymer solution;
[0007] Step 2, dispersing the degradable metal powder into an organic solvent to obtain a suspension of the degradable metal powder;
[0008] Step 3, adding a deionized water solution to the polymer solution obtained in step 1, and then performing ultrasonic emulsification using an ultrasonic device to obtain a polymer emulsion;
[0009] Step 4, mixing and stirring the metal powder suspension prepared in step 2 and the polymer emulsion prepared in step 3 to obtain a composite solution;
[0010] Step 5, curing and drying the composite solution in step 4 to obtain a degradable elastomer material.
[0011] Preferably, in step 1, the degradable polymer material is a degradable elastomeric polymer material, or a mixture of a degradable elastomeric polymer material and a degradable non-elastomeric polymer material;
[0012] When the degradable polymer material is a degradable elastomeric polymer material and a degradable non-elastomeric polymer material, the mass proportion of the degradable elastomeric polymer material in the polymer solution is greater than 5%.
[0013] Preferably, the degradable elastomeric polymer material is PTMC, PGA or PU; the degradable non-elastomeric polymer material is PLA, PLGA or PCL.
[0014] Preferably, in step 1, the degradable polymer material is a degradable non-elastomeric polymer material;
[0015] When the degradable non-elastomeric polymer material is dissolved by an organic solvent, a plasticizer is added.
[0016] Preferably, in step 2, the particle size of the degradable metal powder is less than 1 mm; the degradable metal is zinc, magnesium, zinc alloy or magnesium alloy.
[0017] Preferably, in step 4, the mass content of the degradable metal powder in the composite solution is 5%-80%.
[0018] Preferably, in step 3, the concentration of the deionized water solution is 10%-80% vol.
[0019] Preferably, in step 5, the composite solution is solidified by placing it in a low-temperature environment.
[0020] A degradable elastomer material is prepared by the method for preparing a degradable elastomer material.
[0021] A uterine cavity stent, the uterine cavity stent is obtained by processing the degradable elastomer material;
[0022] The uterine cavity support is evenly provided with a plurality of openings.
[0023] The present invention is beneficial in that:
[0024] The present invention proposes a method for preparing a degradable elastomeric material, wherein the material is completely degradable, and the degradation rate of the material can be adjusted by adjusting the composition and porosity of the composite material to meet different requirements for degradation of uterine cavity stents; at the same time, the elastic modulus of the degradable elastomeric material is close to that of the uterine cavity inner wall tissue, which can avoid abrasion or puncture damage to the uterine cavity inner wall during the implantation process or the degradation process, and the similar elastic modulus can also avoid the problem of fibrosis of the surrounding tissue caused by the mismatch of the implanted stent modulus. The degradable elastomeric material has a good shape memory effect, and can be automatically opened after being implanted into the uterine cavity environment by a catheter intervention method, which greatly reduces the difficulty of the operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0026] Figure 1 The present invention is a flow chart of a method for preparing a degradable elastomer material;
[0027] Figure 2 This is the appearance morphology of the uterine cavity stent obtained by processing and preparing in the embodiment;
[0028] Figure 3 This is a scanning electron microscope image of a degradable elastomer material. DETAILED DESCRIPTION
[0029] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0030] The following detailed description is an exemplary description, which is intended to provide further detailed description of the present invention. Unless otherwise specified, all technical terms used in the present invention have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. The terms used in the present invention are only for describing specific embodiments, and are not intended to limit the exemplary embodiments according to the present invention.
[0031] See also Figure 1 As shown, the present invention provides a method for preparing a degradable elastomer material, wherein the method uses degradable metal powder, degradable elastomer polymer material and degradable non-elastic polymer material as a composite matrix, and then prepares a porous composite material by emulsification pore formation. Specifically, the method comprises the following steps:
[0032] Step 1, dissolving the polymer material with an organic solvent to prepare a uniformly dissolved polymer solution;
[0033] Step 2, dispersing the metal powder in an organic solvent to obtain a suspension of the metal powder;
[0034] Step 3, adding 10%-80% vol of deionized water solution to the polymer solution obtained in step 1, and then performing ultrasonic emulsification using ultrasonic equipment to obtain an emulsion of the polymer solution;
[0035] Step 4, mixing and stirring the metal powder suspension prepared in step 2 and the polymer emulsion prepared in step 3 to obtain a composite solution, wherein the mass content of the degradable metal powder in the composite solution is 5%-80%;
[0036] Step 5, placing the composite solution in step 4 in a freezing environment, and after the composite solution is completely solidified, freeze-drying is performed to obtain a degradable elastomer material.
[0037] In a specific embodiment, the polymer material in step 1 includes a degradable elastomeric polymer material.
[0038] In a specific embodiment, the polymer material in step 1 includes a degradable elastomeric polymer material and a degradable non-elastomeric polymer material; in the polymer solution, the mass proportion of the degradable elastomeric polymer material exceeds 5%.
[0039] In a specific embodiment, the polymer material in step 1 is a degradable non-elastomeric polymer material, and a plasticizer is added to the polymer solution.
[0040] In a specific embodiment, the metal powder is a degradable metal powder, which may be biodegradable metals such as zinc and its alloys, magnesium and its alloys, and the particle size of the metal powder is less than 1 mm.
[0041] In a specific embodiment, the degradable elastomeric polymer material can be polytrimethylene carbonate PTMC, polyglycolide PGA, polyurethane PU, etc.; the degradable non-elastomeric polymer material can be polylactic acid PLA, polylactic acid-glycolic acid copolymer PLGA, semi-crystalline polymer PCL, etc.
[0042] In a specific embodiment, the freezing environment in step 5 is an environment below -20 degrees Celsius, and the storage time can be 12 hours.
[0043] In a specific embodiment, different degradation rates of the degradable elastomer material can be achieved by adjusting the type and molecular weight of the composite polymer and the size of the prepared porosity.
[0044] The present invention also provides a degradable elastomer material, which is prepared by the above-mentioned method for preparing a degradable elastomer material.
[0045] The degradable elastomeric material is completely degradable, and the degradation rate can be adjusted by the composition and porosity of the composite material to meet different degradation requirements of the intrauterine stent.
[0046] The elastic modulus of the degradable elastomeric material is close to that of the uterine cavity inner wall tissue, which can avoid wear or puncture damage to the uterine cavity inner wall during the implantation process or degradation process. The similar elastic modulus can also avoid the problem of surrounding tissue fibrosis caused by mismatch of the implanted stent modulus.
[0047] The degradable elastomeric material has a good shape memory effect and can be automatically opened after being implanted into the uterine cavity environment through a catheter intervention method, which greatly reduces the difficulty of the operation.
[0048] The degradable elastomer material is a composite porous scaffold material, which contains a micro-nano pore structure inside and can be used as a carrier of drug factors to carry functional therapeutic drugs.
[0049] The composite degradable alloy particles in the degradable elastomer material can increase the compressive resistance of the material, and the release of metal ions has good antibacterial properties, thereby avoiding infection after device implantation.
[0050] The present invention also provides a uterine cavity stent, which is prepared from the above-mentioned degradable elastomer material. According to the size requirements of the uterine cavity environment, the degradable elastomer material is processed into a fixed shape by injection molding or cutting, including a variety of elastomer uterine cavity stent structures such as "Y" shape and "O" shape, such as Figure 2 As shown, the elastomeric uterine cavity stent can be implanted into the uterine cavity environment by means of catheter intervention, and can automatically spring open and fit the uterine cavity wall.
[0051] In a specific embodiment, the intrauterine stent is specifically: approximately trapezoidal in shape, with the length of both sides being 36 mm, the length of the upper side being 9 mm, and the length of the lower side being 30 mm.
[0052] In a specific embodiment, a plurality of circular holes are evenly arranged on the intrauterine stent, and the size, shape, density, etc. of the holes can be adjusted according to the requirements of the degradation rate.
[0053] In a specific embodiment, the composite solution prepared in step 4 can be introduced into a prefabricated intrauterine stent mold, and then freeze-dried according to step 5 to obtain the intrauterine stent.
[0054] In a specific embodiment, the composite material of the intrauterine stent with a certain thickness obtained in step 5 can be cut and molded to obtain an intrauterine stent with a desired structure.
[0055] Embodiment 1:
[0056] The metal powder is pure zinc metal powder, and the polymer is PTMC and PLA. Then the processing and preparation are carried out according to the following steps:
[0057] 1) using dichloromethane as an organic solvent to prepare a 4-8 wt % polymer mixed solution, wherein the mass ratio of the two polymers PTMC PLA is 1:1;
[0058] 2) dispersing pure zinc powder particles with a particle size of 15-30 μm in a concentration of 5 g / ml into a dichloromethane solvent to obtain a zinc powder dispersion;
[0059] 3) adding 3 ml of deionized water solution to 5 ml of the polymer solution prepared in step 1), and performing ultrasonic dispersion using a cell disruptor to obtain an emulsion of the polymer solution;
[0060] 4) adding the pure zinc powder dispersion prepared in step 2) to the polymer solution emulsion prepared in step 3) to obtain a composite solution with a ratio of zinc powder to polymer of 1:1;
[0061] 5) Pour the composite solution prepared in step 4) into a container to ensure that the height of the solution is greater than 5 mm; then place it in a -20°C environment and freeze overnight. After the sample is completely solidified, transfer it to a freeze dryer for freeze drying to obtain a porous elastomer composite scaffold material. The microstructure of the composite scaffold material is shown in the attached figure. Figure 3 shown.
[0062] Embodiment 2:
[0063] The metal powder is pure zinc-magnesium alloy metal powder, and the polymer is PTMC and PCL. Then the processing and preparation are carried out according to the following steps:
[0064] 1) using an organic solvent, dichloromethane, to prepare a 6 wt % PTMC solution and a PCL solution, and then mixing the two solutions in a ratio of 1:2 to finally obtain a mixed solution of a polymer solution;
[0065] 2) dispersing pure zinc-magnesium alloy powder particles with a particle size of 15-30 μm in a concentration of 5 g / ml into a dichloromethane solvent to obtain a zinc powder dispersion;
[0066] 3) adding 3 ml of deionized water solution to 5 ml of the polymer solution prepared in step 1), and performing ultrasonic dispersion using a cell disruptor to obtain an emulsion of the polymer solution;
[0067] 4) adding the pure zinc powder dispersion prepared in step 2) to the polymer solution emulsion prepared in step 3) to obtain a composite solution with a ratio of zinc-magnesium alloy powder to polymer of 1:1;
[0068] 5) pouring the composite solution prepared in step 4) into a container to ensure that the height of the solution is greater than 5 mm; then placing it in a -20°C environment for freezing overnight, and after the sample is completely solidified, transferring it to a freeze dryer for freeze drying to obtain a porous elastomer composite scaffold material.
[0069] Embodiment 3:
[0070] The metal powder is pure zinc metal powder, and the polymer is PLA. Then the processing and preparation are carried out according to the following steps:
[0071] 1) Using an organic solvent, dichloromethane, to prepare a 6 wt % PLA solution;
[0072] 2) dispersing pure zinc powder particles with a particle size of 15-30 μm in a concentration of 5 g / ml into a dichloromethane solvent to obtain a zinc powder dispersion;
[0073] 3) adding 4 ml of deionized water solution to 5 ml of the polymer solution prepared in step 1), and performing ultrasonic dispersion using a cell disruptor to obtain an emulsion of the polymer solution;
[0074] 4) adding the pure zinc powder dispersion prepared in step 2) to the polymer solution emulsion prepared in step 3) to obtain a composite solution with a ratio of zinc powder to polymer of 1:1;
[0075] 5) pouring the composite solution prepared in step 4) into a container to ensure that the height of the solution is greater than 5 mm; then placing it in a -20°C environment for freezing overnight, and after the sample is completely solidified, transferring it to a freeze dryer for freeze drying to obtain a porous elastomer composite scaffold material.
[0076] The present invention uses an organic solvent to fully dissolve oil-soluble degradable elastomer polymers and non-elastic polymers to obtain a polymer solution; then disperses biodegradable metal alloy powder into the polymer solution to obtain a suspension of metal powder; finally, the degradable metal powder suspension is prepared into a porous material by emulsification pore formation. According to the structural requirements of the uterine cavity stent, it is further optimized and designed into a variety of elastomeric uterine cavity stent structures such as "Y" shape and "O" shape.
[0077] In the prior art, a balloon with a certain elastic modulus or an intrauterine contraceptive device made of a copper-containing metal material is often used. Both of them are non-degradable and small in size. They cannot well cut off the adhesion of the uterine cavity wall tissue and need to be removed a second time later. The degradable elastomer uterine cavity stent proposed in the present invention has an elastic modulus similar to that of the uterine cavity tissue and will not abrade the uterine cavity tissue. And it can achieve complete degradation of the stent as needed after implantation without the need for secondary removal. The present invention proposes a new solution for the material selection and processing and preparation technology of the uterine cavity stent, which is conducive to the development of new medical devices.
[0078] It is known from common technical knowledge that the present invention can be implemented by other embodiments that do not deviate from its spirit or essential features. Therefore, the above disclosed embodiments are only illustrative in all respects and are not exclusive. All changes within the scope of the present invention or within the scope equivalent to the present invention are included in the present invention.
[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a degradable elastomeric material, characterized in that: The steps include: Step 1, dissolving the degradable polymer material with an organic solvent to prepare a uniformly dissolved polymer solution; Step 2, dispersing the degradable metal powder into an organic solvent to obtain a suspension of the degradable metal powder; Step 3, adding a deionized water solution to the polymer solution obtained in step 1, and then performing ultrasonic emulsification using an ultrasonic device to obtain a polymer emulsion; Step 4, mixing and stirring the metal powder suspension prepared in step 2 and the polymer emulsion prepared in step 3 to obtain a composite solution; Step 5, curing and drying the composite solution in step 4 to obtain a degradable elastomer material.
2. The method for preparing a degradable elastomer material according to claim 1, characterized in that: In the step 1, the degradable polymer material is a degradable elastomeric polymer material, or a mixture of a degradable elastomeric polymer material and a degradable non-elastomeric polymer material; When the degradable polymer material is a degradable elastomeric polymer material and a degradable non-elastomeric polymer material, the mass proportion of the degradable elastomeric polymer material in the polymer solution is greater than 5%.
3. The method for preparing a degradable elastomer material according to claim 2, characterized in that: The degradable elastomeric polymer material is PTMC, PGA or PU; the degradable non-elastomeric polymer material is PLA, PLGA or PCL.
4. The method for preparing a degradable elastomer material according to claim 1, characterized in that: In the step 1, the degradable polymer material is a degradable non-elastic polymer material; When the degradable non-elastomeric polymer material is dissolved by an organic solvent, a plasticizer is added.
5. The method for preparing a degradable elastomer material according to claim 1, characterized in that: In step 2, the particle size of the degradable metal powder is less than 1 mm; the degradable metal is zinc, magnesium, zinc alloy or magnesium alloy.
6. The method for preparing a degradable elastomer material according to claim 1, characterized in that: In the step 4, the mass content of the degradable metal powder in the composite solution is 5%-80%.
7. The method for preparing a degradable elastomer material according to claim 1, characterized in that: In step 3, the concentration of the deionized water solution is 10%-80% vol.
8. The method for preparing a degradable elastomer material according to claim 1, characterized in that: In the step 5, the composite solution is solidified by placing it in a low temperature environment.
9. A degradable elastomeric material, characterized in that: The material is prepared by the method for preparing a degradable elastomer material according to any one of claims 1-8.
10. A uterine cavity stent, characterized in that: The uterine cavity stent is made by processing the degradable elastomer material described in claim 9; The uterine cavity support is evenly provided with a plurality of openings.